An integrated system of sinusoidal-corrugated plate heat exchanger and thermoelectric modules for wastewater heat recovery. (1st September 2022) - Sun, Yajing; Zhai, Pengcheng; Ning, Jiuxin; Zheng, Chenggang; Zhang, Shengwu; Liu, Changyong; Yan, Wentao
Graphical abstract: Highlights: An integrated system of sinusoidal-corrugated heat exchanger and thermoelectric modules is designed and investigated for industrial wastewater heat recovery. The sinusoidal-corrugated heat exchanger prototype is fabricated by laser powder bed fusion technology. The sinusoidal-corrugated heat exchanger has a maximum heat transfer effectiveness of 70.94%. The maximum net output power of system with sinusoidal-corrugated heat exchanger can reach 0.5 W. Abstract: This paper describes a new integrated system of sinusoidal-corrugated plate heat exchanger (SPHX) and thermoelectric modules (TEMs) applied in industrial wastewater heat recovery (IWWHR). The TEMs are mounted inside the baffles of SPHX, which is beneficial to minify the entire system volume and reduce the impact of TEMs on the heat transfer of SPHX. The complex SPHX prototype is fabricated by laser powder bed fusion (LPBF) technology and employed to validate the accuracy of built numerical SPHX model. To highlight the superior performance of designed SPHX, its capabilities on heat transfer are compared with a baseline plate heat exchanger (BPHX). The results show that the sinusoidal-corrugated structure is more beneficial for inducing vortices in the flow field. And the maximum heat transfer efficiency and overall heat transfer coefficient of SPHX can reach 70.94% and 2036.531 W/(m 2 ⋅K), respectively, better than those of BPHX. The calculations of net output power show that enough output power can be generated to offset the pumping power of all working media in both the systems of SPHX and BPHX, indicating that the integrated system with SPHX and TEMs is appropriate to recover the heat from industrial wastewater. This study opens a new avenue for the design of HX and TEMs applied in IWWHR.